Pulmonary rehabilitation referral and uptake from primary care for people living with COPD: a mixed-methods study. Issue 1 (17th February 2020) - Early, Frances; Wilson, Patricia Mary; Deaton, Christi; Wellwood, Ian; Haque, Hena Wali; Fox, Sarah Emma; Yousaf, Azka; Meysner, Oliver D.; Ward, James R.; Singh, Sally J.; Fuld, Jonathan Paul
Pulmonary rehabilitation (PR) for people with COPD leads to clinically significant improvements in quality of life and exercise capacity [1]. In England and Wales, UK, in 2013–2014, only 15% of eligible patients were referred (51% from primary care), of whom 31% did not attend assessment [2]. We aimed to generate a theory-informed understanding of enablers and barriers to PR referral and uptake from primary care. Healthcare service and patient barriers contribute to low referral to and uptake of pulmonary rehabilitation (PR). Solutions should support skilled clinician–patient conversations and span primary care–PR boundaries to prevent disjointed working. http://bit.ly/2PVKHZf